An implementation framework for evaluating the biocidal potential of essential oils in controlling Fusarium wilt in spinach: from in vitro to in planta - Mirmajlessi, Mahyar; Najdabbasi, Neda; Sigillo, Loredana; Haesaert, Geert (Frontiers in Plant Science, 2024)
Fusarium wilt, caused by Fusarium oxysporum f. sp. spinaciae, causes a significant challenge on vegetative spinach and seed production. Addressing this issue necessitates continuous research focused on innovative treatments and protocols through comprehensive bioassays. Recent studies have highlighted the potential of plant-based compounds in controlling fungal diseases. The present work aims to conduct a series of experiments, encompassing both in vitro and in planta assessments, to investigate the biocontrol capabilities of different essential oils (EOs) at various application rates, with the ultimate goal of reducing the incidence of Fusarium wilt in spinach. The inhibitory effect of four plant EOs (marjoram, thyme, oregano, and tea tree) was initially assessed on the spore germination of five unknown Fusarium strains. The outcomes revealed diverse sensitivities of Fusarium strains to EOs, with thyme exhibiting the broadest inhibition, followed by oregano at the highest concentration (6.66 μL/mL) in most strains. The tested compounds displayed a diverse range of median effective dose (ED50) values (0.69 to 7.53 µL/mL), with thyme and oregano consistently showing lower ED50 values. The direct and indirect inhibitory impact of these compounds on Fusarium mycelial growth ranged from ~14 % to ~100 %, wherein thyme and oregano consistently exhibiting the highest effectiveness. Following the results of five distinct inoculation approaches and molecular identification, the highly pathogenic strain F-17536 (F. oxysporum f.sp. spinaciae) was chosen for Fusarium wilt assessment in spinach seedlings, employing two promising EO candidates through seed and soil treatments. Our findings indicate that colonized grain (CG) proved to be a convenient and optimal inoculation method for consistent Fusarium wilt assessment under greenhouse conditions. Seed treatments with thyme and oregano EOs consistently resulted in significantly better disease reduction rates, approximately 54 % and 36 % respectively, compared to soil treatments (P > 0.05). Notably, thyme, applied at 6.66 µL/mL, exhibited a favorable emergence rate (ERI), exceeding seven, in both treatments, emphasizing its potential for effective disease control in spinach seedlings without inducing phytotoxic effects. This study successfully transitions from in vitro to in planta experiments, highlighting the potential incorporation of EOs into integrated disease management for Fusarium wilt in spinach production.